Hybrid event beds generated by erosional bulking of modern hyperpycnal flows on the Choshui River delta front, Taiwan Strait. Issue 6 (24th April 2021) - Jin, Lina; Shan, Xin; Shi, Xuefa; Fonnesu, Marco; Qiao, Shuqing; Kandasamy, Selvaraj; Wang, Huawei; Liu, Shengfa; Fang, Xisheng; Zou, Xinqing
Abstract: Hyperpycnal flows are important agents for transporting detrital sediments from rivers to oceans. Previous studies often assumed that the deposits of flood‐controlled delta fronts would be dominated by graded sand with common hummocky cross‐stratification. This study documents, for the first time, hybrid event beds and plumite deposits inside the succession of a modern delta front. This delta in the Taiwan Strait is fed by the Choshui River, which is considered a highly efficient sediment transport system with individual floods with extremely high suspended sediment concentrations. The deltaic event beds recorded in the core were interpreted as hyperpycnal flow‐generated hybrid event beds and turbidites triggered by hypopycnal flows. Accelerator Mass Spectrometry 14 C dating, grain‐size analysis and measurements of stable isotopic composition of organic matter were conducted to delineate the depositional process of the recognized beds. The internal subdivisions of the hybrid event beds were differentiated mainly based on sedimentary textures, including cohesive mud content, sand content and sorting. The disorganized portion (division H3) appears internally chaotic and contains large rafted substrate clasts but also displays an upward increase in dispersed cohesive mud from 35% (division H3a) to 50% (division H3b). In contrast, massive H1 divisions are characterized by much lower cohesive mud of ca 8%. The vertical arrangement between depositional facies allows the discrimination of three hybrid event bed types. The stable carbon isotopic composition of the organic matter reveals that the cohesive mud in each division of the hybrid event beds was sourced from marine substrate, rather than supplied by the original hyperpycnal flows. Therefore, the hybrid event beds are generated by energetic hyperpycnal flows, which can delaminate the muddy sea‐floor and incorporate large quantities of substrate fragments. The bulking of erosional hyperpycnal turbulent flow forces flow transformation and generates a more cohesive flow with a turbulent, dense head and trailing bipartite debris flow. The occurrence of hybrid event beds in modern shallow delta front settings is also an important novelty, implying a high density of hyperpycnal flows at the mouth of sediment‐laden rivers as well as the crucial impact of substrate entrainment on the development of hybrid event beds.